A note on the recent sighting of Zosterops flava Javan White-eye - G Allport; G R Milton (KUKILA, 1988)
A selection of sites on the north coast of West Java was surveyed for White-eyes Zosterops between March 1984 and December 1985. Javan White-eye Zosterops f1ava was recorded at Pulau Dua, Muara Gembong and Tanjung Sedari. White-eyes were not seen at Pulau Rambut, Muara Angke, or on the coast between Indramayu and Cirebon. z. flava was seen only once in mangrove, preferring relic stands of coastal forest. This favoured habitat is now much reduced and fragmented, and remains under further human pressure, thus z. F1ava should be 1isted as threatened in Java.